Dalai Lama man, monk, mystic - Chhaya, Mayank (Doubleday, an imprint of The Doubleday Broadway Publishing Group, 2007)
Drawing on personal interviews, provides a portrait of one of the world's most important religious figures, offering a study of Tibet and its Buddhist traditions, the forces that shaped his beliefs, his role in exile, and the future of Tibet.